Meta-Analysis of the Prevalence of Echinococcus in Sheep in China From 1983 to 2020 - Gao, Yang; Wang, Wei; Lyu, Chuang; Wei, Xin-Yu; Chen, Yu; Zhao, Quan; Ran, Zhi-Guang; Xia, You-Qing (Frontiers in Cellular and Infection Microbiology, 2021)
Echinococcosis is a zoonosis caused by the larval stage of cestode species that belong to the genus Echinococcus. The infection of hydatid in sheep is very common in China, especially in the northwestern China. Here, we conducted the first systematic review and meta-analysis of echinococcosis in sheep in China. Six databases (PubMed, ScienceDirect, Baidu Library, CNKI, Wanfang, and VIP Chinese Journal Database) were used to retrieve the literatures on echinococcosis in sheep in China from 1983 to 2020, and 74 studies. The random effects model was used in the “meta” package of the R software and the PFT was chosen for rate conversion. The research data were analyzed through subgroup analysis and univariate meta-regression analysis to reveal the factors that lead to research heterogeneity. The combined prevalence of Echinococcus in the selected period was estimated to be 30.9% (192,094/826,406). In the analysis of sampling year, the lowest positive rate was 13.9% (10,296/177,318) after 2011. The highest prevalence of Echinococcus was 51.1% (278/531) in the southwestern China. The highest infection rate in sheep was 20.1% (58,344/597,815) in the liver. The analysis based on age showed that the infection rate of elderly sheep was significantly higher than that in younger animals (P < 0.05). We also evaluated the effects of different geographic and climatic factors on the prevalence of Echinococcus in sheep. The results showed that the prevalence of Echinococcus was higher in high altitude, cold, humid, and high rainfall areas. It is necessary to carry out long-term monitoring and control of echinococcosis, cut off the infection route, and reduce the risk of infection in the high risk areas.